Penggunaan Limbah Gypsum dan Limbah Karbit Sebagai Substitusi Semen Terhadap Campuran Beton - Triyana Vivin Wagio; Jonie Tanijaya; Desi Sandy (Program Studi Teknik Sipil UKI Paulus-Makassar, 2023)
Carbide waste is the residue of carbide combustion where carbide waste has a similar content with cement. Gypsum waste is a remnant of the gypsum profiling industry. The purpose of the study is to determine the value and how the relationship affects the compressive, strength, tensile strength of splitting, and modulus of elasticity by using 5% gypsum waste and 8% and 12% carbide waste variations as substitution materials in cement . The research conducted is experimental on concrete mixtures. The planned concrete quality is 30 MPa with a test life of 3, 7.21, and 28 days with a 5% variation in gypsum waste and a variation in carbide waste of 0%, 8%, and 12%. Based on the results of compressive strength testing at 28 days for variations of 0%, 8%, and 12% obtained values of 31,038 MPa, 31,507 MPa, and 32,277 MPa. The results of the tensile strength test at variations of 0%, 8%, and 12% obtained values of 2,854 MPa, 2,902 MPa, and 2,996 MPa. In the modulus elaticity test at variations of 0%, 8%, and 12% obtained results of 27903,497 MPa, 30328,111 MPa, and 31570,793 MPa. In tests of compressive strength, split tensile strength, and modulus of elasticity obtained maximum values at a variation of 12%. With the relationship of compressive strength and tensile strength, results are obtained that are directly proportional to the increase in the percentage of carbide welding waste as well as the relationship of compressive strength and modulus of elasticity, results are obtained that are directly proportional to the increase in the percentage of carbide welding waste. The results show that the use of gypsum waste and carbide welding waste can increase the strength of concrete.